EVALUASI LANDASAN ILMU PENGETAHUAN DALAM PENGEMBANGAN KURIKULUM BERBASIS KOMPETENSI PADA PENDIDIKAN DASAR - Andriani, Yuli; Effy Mulyasari; Deri Hendriawan; Eti Nurhayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The  competency-based  curriculum  represents  an  educational  framework  that  aims  to  foster  students  understanding,  abilities,  and  values  in  a  holistic  manner.  Creating  such  a  curriculum  relies  heavily  on  scientific  principles  that  provide  the  foundation  for  establishing  learning  goals,  subject  matter,  instructional  strategies,  and  evaluation  techniques.  This  investigation  seeks  to  examine  how  scientific  principles  contribute  to  designing  a  competency-based  curriculum  for  primary  education.  The  study  uses  a  library  research  approach  by  examining  and  interpreting  related  materials  such  as  books,  scholarly  articles,  curriculum  frameworks,  and  educational  regulations.  The  results  demonstrate  that  scientific  principles  are  vital  in  maintaining  curriculum  content  that  aligns  with  developments  in  science,  technology,  and  societal  demands.  They  also  aid  in  cultivating  analytical  thinking,  problem-solving  capabilities,  and  continuous  that  aligns  with  developments  in  science,  technology,  and  societal  demands.  learning  among  learners.  Nevertheless,  incorporating  scientific  principles  into  curriculum  design  presents  various  obstacles,  such  as  the  disconnect  between  theoretical  ideas  and  actual  teaching  methods,  insufficient  teacher  expertise,  and  the  swift  rate  of  scientific  and  technological  advancements.  Consequently,  ongoing  curriculum  assessment  and  refinement  are  required  to  preserve  its  appropriateness  and  success  in  accomplishing  educational  objectives.  The  study  determines  that  reinforcing  scientific  principles  is  crucial  for  improving  the  quality  of  competency-based  curriculum  execution  in  primary  education.